Churches and violence in north-eastern Guatemala: Between safe space and lions' pit. (September 2019) - Simon, Saskia
Based on an ethnographic research led in north-eastern Guatemala between 2011 and 2013, this article problematizes the idea usually advanced in sociology of religions that churches represent safe spaces allowing the reconstruction of social fabric in violent contexts. Analyzing collective mechanisms of 'living together' in this region, the author shows the specific role of the Catholic and Evangelical Churches as spaces where struggles have taken place, but where they nevertheless represent safe spaces for expression.